The emerging business models in the digital economy - Porsayev G. (Research Parks Publishing LLC, 2020)
The article highlights various business models in the modern economy under the circumstances of the digital economy. In particular, the impact of digitalization in sectors of retail, healthcare, manufacturing, education and others are discussed